Integrated analysis of young swimmers' sprint performance - Silva, A. F.; Figueiredo, P.; Ribeiro, J.; Alves, F.; Vilas-Boas, J. P.; Seifert, L.; Fernandes, R. J. (Motor control, 2019)
To analyze young swimmers' performance regarding sex and skill level, 23 boys and 26 girls (15.7±0.8 and 14.5±0.8 years old, respectively) were assessed for anthropometry, flexibility, strength, drag, coordination, and biomechanical variables. During a 50-m maximal front-crawl bout, seven aerial and six underwater Qualisys cameras assessed kinematics, and a load cell was used to measure drag (Tedea, United Kingdom) and tethered swimming force. A multivariate analysis of variance test (p<.05) enabled us to observe differences between skill levels in speed, stroke frequency, stroke index, and intracyclic velocity variations, but most relevant differences were noticed when comparing sexes, particularly for anthropometrics, shoulder flexibility, speed, stroke frequency, stroke length, drag, mechanical power, power per stroke, and maximal and mean force. Considering the included variables, only male swimmers' performance could be predicted through multiple linear regression, with stroke index, left shoulder flexion, and intracycle velocity variations showing great importance in achieving better results.